PEMANFAATAN TANAMAN REFUGIA TERHADAP INTENSITAS SERANGAN HAMA KUTU KEBUL (Bemisia tabaci) TANAMAN KEDELAI EDAMAME (Glycine max (L.) Merill) SEBAGAI SUMBER BELAJAR BIOLOGI BERUPA POSTER - Rista, Paulina Eva; Susanto, Agus; Anak Agung Oka (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2025)
The objectives of this study are: 1) To determine the benefits of refugia plants (Zinnia elegans Jacq. and Cosmos caudatus) on the intensity of whitefly (Bemisia tabaci) infestation in edamame soybean (Glycinemax (L.) Merrill) plants, 2) To examine the relationship between edamame soybean plant damage (Glycine max (L.) Merrill) and the harvest results, and 3) To evaluate the research results in the form of a poster that is suitable for use as a biology learning resource. This research uses both descriptive qualitative and quantitative methods. The study employs two treatments: edamame soybean fields planted with refugiaplants and edamame soybean fields without refugia plants. The data were analyzed using pest infestationintensity analysis and the Independent Sample T-Test. Based on the research results, the use of refugia plants had a beneficial effect on reducing the intensity ofwhitefly infestations in edamame soybean plants. The intensity analysis showed that refugia plants are effective in suppressing whitefly infestation. Based on T-test analysis, there was no significant difference in the harvest yield of edamame soybeans between fields with and without refugia plants. The validation analysis of the learning resource indicates that this study is suitable as a biology learning resource in the form of a poster.